A systematic review of augmented reality tourism research: What is now and what is next?. (January 2021) - Jingen Liang, Lena; Elliot, Statia
The application of augmented reality in tourism is flourishing and promising, bringing an emerging body of studies. While virtual reality might be a virtual threat to the travel and tourism as being a potential substitute, augmented reality allows users to interact with the real environment that could potentially enhance visitors' experience. Distinguishing from reviews that combine studies of augmented reality and virtual reality, this study systematically investigates the current state of augmented reality research exclusively in the tourism literature. The results identify five established and emerging research clusters, with one predominant cluster that focuses on user acceptance of augmented reality, commonly applying the technology acceptance model. A meta-analysis of a subset of four empirical studies reveals that perceived ease of use has an overall influence of 52.79% on perceived usefulness. Lastly, a concept map visually presents the constructs that have been explored across the clusters. Based on our review, future research directions are proposed to advance knowledge in the emerging area of gamification, to explore the potential negative consequences of augmented reality, and to apply more innovative methods and study designs.